IMF Staff papers : Volume 36 No. 1. (IMF Staff Papers; IMF Staff Papers ;, 1989)
The determinants of current account imbalances under floating exchange rates are analyzed. The analysis provides a framework within which the sources of. and the remedies for, the current account imbalances between the United States, Japan, and the Federal Republic of Germany can be discussed. The effects of various government policies are emphasized, in particular the differences between expenditure-changing and expenditure-switching policies. Short-run and long-run considerations are investigated, as well as the role played by expectations and price-level dynamics.